Exploring key factors of pilot projects in agile transformation process using a grounded theory study - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abd Ghani, Abdul Azim; Md. Sultan, Abu Bakar; Sharif, Khaironi Yatim (Springer, 2013)
Changing development approach from disciplined to agile methods is an organizational mutation that requires many issues to be considered to increase its chance of success. Selecting an appropriate pilot project as initial project that is going to be done through an Agile method is a critical task. Due to the impact of such a pilot project on successful Agile transformation, understanding its critical factors helps organizations choose the most suitable project to start Agile transition. Conducting a Grounded Theory, showed that organization should considered some key factors of a pilot : criticality, duration, size and required resources. Besides these factors, the results showed that organization should be aware of the risk of successful pilot project in their next Agile projects. The study also showed that pilot selection mostly is done by Agile coaches or is forced by customer.